Relación entre estilos parentales y desarrollo de la autoestima en adolescentes - Flores Talavera, Paula Estefania (2021)
Adolescence is a crucial stage in human development in which the interaction between parenting styles and the development of self-esteem can have a protective effect on the development of this population. A systematic search was carried out following some of the guidelines of the PRISMA (Urrutia & Bonfill, 2013) to collect updated information on the relationship between both variables. The databases consulted were Proquest, Scopus, PubMed and Scielo. Seven studies, that evaluated parenting styles and selfesteem in adolescents aged 12 to 19 years, were selected. The methodology used was correlational analysis between the results of WASC and PCS scales for the evaluation of parenting styles, and RSE or AF5 for the measurement of self-esteem. The results indicated that there is a relationship between parenting styles and self-esteem in adolescents. In general, the articles indicate that the permissive style is associated with the highest levels of self-esteem, and, at a lower level, the authoritative style is also associated with this variable; while the authoritarian and negligent styles are related to the lower levels of self-esteem in this population.